Initial clinical and treatment patterns of advanced differentiated thyroid cancer: ERUDIT study. Issue 5 (11th August 2022) - Vallejo Casas, Juan Antonio; Sambo, Marcel; López López, Carlos; Durán-Poveda, Manuel; Rodríguez-Villanueva García, Julio; Santos, Rita Joana; Llanos, Marta; Navarro-González, Elena; Aller, Javier; Pubul, Virginia; Guadalix, Sonsoles; Crespo, Guillermo; et al.
Abstract : Background: Up to 30% of differentiated thyroid cancer (DTC) will develop advanced-stage disease (aDTC) with reduced overall survival (OS). Objective: The aim of this study is to characterize initial diagnosis of aDTC, its therapeutic management, and prognosis in Spain and Portugal. Methods: A multicentre, longitudinal, retrospective study of adult patients diagnosed with aDTC in the Iberian Peninsula was conducted between January 2007 and December 2012. Analyses of baseline characteristics and results of initial treatments, relapse- or progression-free survival ((RP)FS) from first DTC diagnosis, OS, and prognostic factors impacting the evolution of advanced disease were evaluated. Results: Two hundred and thirteen patients (median age: 63 years; 57% female) were eligible from 23 hospitals. Advanced disease presented at first diagnosis ( de novo aDTC) included 54% of patients, while 46% had relapsed from early disease (recurrent/progressive eDTC). At initial stage, most patients received surgery (98%) and/or radioiodine (RAI) (89%), with no differences seen between median OS (95% CI) (10.4 (7.3–15.3) years) and median disease-specific-survival (95% CI) (11.1 (8.7–16.2) years; log-rank test P = 0.4737). Age at diagnosis being <55 years was associated with a lower risk of death (Wald chi-square (Wc-s) P < 0.0001), while a poor response to RAI to a higher risk of death ((Wc-s) P < 0.05). In the eDTC cohort, median (RP)FS (95% CI) was of 1.7 (1.0–2.0) years after RAI, with R0/R1 surgeries being the only common significant favourable factor for longer (RP)FS and time to aDTC ((Wc-s) P < 0.05). Conclusion: Identification of early treatment-dependent prognostic factors for an unfavourable course of advanced disease is possible. An intensified therapeutic attitude may reverse this trend and should be considered in poor-performing patients. Prospective studies are required to confirm these findings.